Charting the landscape of priority problems in psychiatry, part 2: pathogenesis and aetiology. (January 2016) - Stephan, Klaas E; Binder, Elisabeth B; Breakspear, Michael; Dayan, Peter; Johnstone, Eve C; Meyer-Lindenberg, Andreas; Schnyder, Ulrich; Wang, Xiao-Jing; Bach, Dominik R; Fletcher, Paul C; Flint, Jonathan; Frank, Michael J; et al.
Summary: This is the second of two companion papers proposing priority problems for research on mental disorders. Whereas the first paper focuses on questions of nosology and diagnosis, this Personal View concerns pathogenesis and aetiology of psychiatric diseases. We hope that this (non-exhaustive and subjective) list of problems, nominated by scientists and clinicians from different fields and institutions, provides guidance and perspectives for choosing future directions in psychiatric science.